Integrated CFD simulation of concentration polarization in narrow membrane channel - Ahmad, A.L. (PERGAMON-ELSEVIER SCIENCE LTD, THE BOULEVARD, LANGFORD LANE, KIDLINGTON, OXFORD OX5 1GB, ENGLAND, 2005)
Numerous analyses on the mass transfer phenomena and hydrodynamics for the fluid adjacent to the membrane have been studied and visualized by computational fluid dynamics (CFD) mathematical modeling and simulation. The availability of CFD simulation study to reveal the concentration polarization profile in the membrane channel, which considering hydrodynamics and membrane transport properties is found to be limited. The main goal of this paper is targeted to the utilization of CFD simulation using commercial CFD package FLUENT to predict the concentration polarization profile, mass transfer coefficient and wall shear stress under different types of conditions in the empty narrow membrane channel. The permeation conditions such as permeation flux and mass fraction have been taken into account in the solution of the governing equations. Simulation results show that the concentration polarization phenomena can be reduced by increasing feed Reynolds number. The decrease of wall shear stress also contributes to the formation of the concentration polarization layer along the membrane surface. The simulated results were validated and compared with the literature data, showing a satisfactory agreement.